Bright Greenish Yellow Fluorescence and Aflatoxins (Biological Sciences - PJSIR, 1997)
Contamination of oil seeds with aflatoxins may cause hazardsto animals and human beings through contamination ofpoultry products and the milk of milch cattle. This study wasundertaken to design a method to detect aflatoxin contaminationby a simple and rapid test i.e. BGYF test or black lighttechnique.